Hyperreality, simulacra and simulations in virtual space as a phenomenon of «antisocial» theory by Jean Baudrillard - V. Novikov; S. Kovaleva (Цифровая социология)
An attempt has been made to apply the scientific approaches of Jean Baudrillard’s anti-social theory, as well as the concepts of hyperreality, simulacra and simulation, used by him for the understanding of social phenomena, occurences and processes in the modern virtual space. The following interpretation of the characteristics of the Internet space has been proposed: a) the Internet can be considered within the framework of Jean Baudrillard’s concept as an example of antireality, since it is possible to preserve anonymity, invent a new life, use other people’s photos, etc.; b) communication in the virtual Internet is, in its essence, a simulation of communication, that is, its surrogate (simulacrum); in this case, the former contact form of communication is replaced by indirect – communication is carried out through social networks and messengers; c) there is a depletion of content and primitivization of expression of emotions, as in virtual communication uses a set of standard phrases, standard themes, emoticons, pictures, exchange of memes and other simulacra that are included in everyday social practices. On the example of the analysis of the results of the sociological research project, implemented at the State University of Management, the practical procedures of their interpretation within the framework of the scientific concept of Jean Baudrillard have been carried out. For example, it has been revealed, that despite the life experience of respondents in the majority of fake Internet content, they all also largely feel comfortable in  a virtual, potentially dangerous environment. Moreover, this environment becomes vital for them: young people spread their lives, their thoughts, desires, value systems, hidden hopes and dreams on public display. This image of social activity becomes for the majority so necessary element of self-realization, that ceases to be a part of this process, and becomes independent, integral, lying outside the person phenomenon.